2014
DOI: 10.22610/jebs.v6i2.473
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Spending and Consumer Confidence in South Africa: Cointegration Analysis

Abstract: The study uses the time series data covering the period 1980Q1 to 2012Q3 to test the existence of any possible long run relationship between consumer spending and consumer confidence in South Africa. The analysis is done using the Vector Auto-Regressive (VAR) model, with the unit root and the direction of causation also tested before any inference can be concluded on this relationship. The unit root tests using the DF-GLS as well as the Ng-Peron show that consumer spending, consumer confidence and economic gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Most studies cover one country (mostly the US or countries within the EU region) or a selected group of EU countries, while evidence for emerging economies remains scarce. Exceptions are represented, for instance, by Khumalo ( 2014 ) who found a positive effect of the consumer confidence on consumers’ behavior in South Africa. Campelo et al ( 2020 ) and Ghosh ( 2021 ) looked at consumer spending in Brazil and found that unemployment changes, stock market fluctuations, interest rate variation, and alterations in the CCI affect consumer spending, making the CCI a good predictor of spending in Brazil.…”
Section: Consumer Confidence and Its Measurementmentioning
confidence: 99%
“…Most studies cover one country (mostly the US or countries within the EU region) or a selected group of EU countries, while evidence for emerging economies remains scarce. Exceptions are represented, for instance, by Khumalo ( 2014 ) who found a positive effect of the consumer confidence on consumers’ behavior in South Africa. Campelo et al ( 2020 ) and Ghosh ( 2021 ) looked at consumer spending in Brazil and found that unemployment changes, stock market fluctuations, interest rate variation, and alterations in the CCI affect consumer spending, making the CCI a good predictor of spending in Brazil.…”
Section: Consumer Confidence and Its Measurementmentioning
confidence: 99%